Genome-wide association mapping of quantitative trait loci for chalkiness-related traits in rice (Oryza sativa L.) - Xu, Qing; Jiang, Jianhua; Jing, Chunyu; Hu, Changmin; Zhang, Mengyuan; Li, Xinru; Shen, Jiaming; Hai, Mei; Zhang, Ying; Wang, Dezheng; Dang, Xiaojing (Frontiers in Genetics, 2024)
Grain chalkiness directly affect the commercial value of rice. The genes related to chalkiness reported so far have been discovered from mutants, but whether these genes can be used to improve rice quality in breeding has not been reported. Therefore, discovering more QTLs/Genes related to chalkiness in rice germplasm is necessary. In this study, we performed a genome-wide association study on the degree endosperm chalkiness (DEC) and the percentage of grains with chalkiness (PGWC) combining the 1.2 million single nucleotide polymorphism (SNPs) with the phenotypic data of 173 rice accessions. Thirteen QTLs for DEC and nine for PGWC were identified, of which four were detected simultaneously for DEC and PGWC. The QTL qDEC11/qPGWC11 was identified as the major QTL. Combining the linkage disequilibrium analysis and SNP information, LOC_Os11g10170 was identified as the candidate gene for DEC. There were significant difference among haplotypes of LOC_Os11g10170, and the Hap 1 of LOC_Os11g10170 can reduce the DEC by 6.19%. The results of qRT-PCR showed that the gene expression level in the accessions with high DEC were significantly larger than that of the accessions with low DEC from 21d to 42d after flowering, reaching a maximum at 28d. These results provide molecular markers and germplasm resources for genetic improvement of chalkiness-related traits.